PENGARUH PENDIDIKAN, PELATIHAN DAN KOMPETENSI SDM TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA BADAN PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN SUMENEP - Nurul Hidayah Khairany (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This research is to analysis the education, training and HR competence variables on employee performance with motivation as a mediating variable (study on the Regional Revenue, Financial and Asset Management Agency of Sumenep Regency). This type of research is explanatory research, the research approach uses a quantitative approach, and the data analysis technique uses Generalized Structured Component Analysis (GeSCA). The research sample was 86 people. The results showed education variable has a good internal reliability consistency because it is greater than 0.6. The results of data analysis using the GeSCA method show that the alpha value obtained is 0.7909, which means that the training variable has a good internal reliability consistency because it is greater than 0.6. The results of data analysis using the GeSCA method show that the alpha value obtained is 0.695, which means that the HR competency variable has a good internal reliability consistency because it is greater than 0.6. The results of data analysis using the GeSCA method show that the alpha value obtained is 0.9071, which means that the motivation variable has a good internal reliability consistency because it is greater than 0.6. The results of data analysis using the GeSCA method show that the alpha value obtained is 0.9082, which means that the employee performance variable has a good internal reliability consistency because it is greater than 0.6.